Design and synthesis of (E)-1, 2-diphenylethene-based EZH2 inhibitors. Issue 5 (1st March 2020) - He, Hualong; Hu, Xi; Teng, Fei; Liu, Zhihao; Zhang, Qiangsheng; Feng, Zhanzhan; Feng, Qiang; Yu, Luoting
Graphical abstract: Abstract: Enhancer of zeste homolog 2 (EZH2) serves as the catalytic subunit of the polycomb repression complex 2 (PRC2), which is implicated in cancer progression metastasis and poor prognosis. Based on our EZH2 inhibitor SKLB1049 with low nanomolar activity, we extended the "tail" region to get a series of ( E )-1, 2-diphenylethene derivatives as novel EZH2 inhibitors. SAR exploration and preliminary assessment led to the discovery of the potent novel EZH2 inhibitor 9b (EZH2 WT IC50  = 22.0 nM). Compound 9b inhibited the proliferation of WSU-DLCL2 and SU-DHL-4 cell lines (IC50  = 1.61 µM and 2.34 µM, respectively). The biological evaluation showed that 9b was a potent inhibitor for wild-type EZH2 and greatly reduced the overall levels of H3K27me3 in a concentration-dependent manner. Further study indicated that 9b could significantly induce apoptosis of SU-DHL-4 cells. These findings indicated that 9b would be an attractive lead compound for further optimization and evaluation.